2011
DOI: 10.1258/ebm.2011.011221
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of allergic airway inflammation in a mouse model of asthma by exogenous mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) have significant immunomodulatory effects in the development of acute lung inflammation and fibrosis. However, it is still unclear as to whether MSCs could attenuate allergic airway inflammation in a mouse model of asthma. We firstly investigated whether exogenous MSCs can relocate to lung tissues in asthmatic mice and analyzed the chemotactic mechanism. Then, we evaluated the in vivo immunomodulatory effect of exogenous MSCs in asthma. MSCs (2 × 10(6)) were administered through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 20 publications
2
44
1
Order By: Relevance
“…We and others have found that in mouse models of mild Th2-eosinophilic mediated AAI, systemic administration of MSCs either during initial sensitization or during challenge significantly ameliorates both AHR and lung inflammation [27][28][29][30][31][32][33][34][35][36][37][38]. In the current study, we demonstrated that systemic MSC administration during challenge ameliorates AHR and lung inflammation in a more severe model of acute mixed Th2/Th17-mediated neutrophilic AAI induced by mucosal exposure to and challenge with adjuvant-free AHE.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We and others have found that in mouse models of mild Th2-eosinophilic mediated AAI, systemic administration of MSCs either during initial sensitization or during challenge significantly ameliorates both AHR and lung inflammation [27][28][29][30][31][32][33][34][35][36][37][38]. In the current study, we demonstrated that systemic MSC administration during challenge ameliorates AHR and lung inflammation in a more severe model of acute mixed Th2/Th17-mediated neutrophilic AAI induced by mucosal exposure to and challenge with adjuvant-free AHE.…”
Section: Discussionsupporting
confidence: 64%
“…With respect to asthma, MSCs have been demonstrated to ameliorate experimentally induced T helper cell (Th) type 2-mediated eosinophilic allergic airway inflammation (AAI) in mice [27][28][29][30][31][32][33][34][35][36][37][38]. Immunogens investigated in models include sensitization and challenge with ovalbumin, ragweed pollen, dust mite antigen, and toluene diisocyanate, and comparable effects have been observed with syngeneic, allogeneic, or xenogeneic MSC administration.…”
Section: Introductionmentioning
confidence: 99%
“…One exception was the group treated before sensitization in the Sun et al [17] study. However, treatment with MSCs before sensitization did decrease BAL total cell count in the Kavanagh [25] and Goodwin [20] studies. The other exception was the recurrent inflammation group in the Lathrop [13] study [13].…”
Section: Bal Total Cell Countmentioning
confidence: 86%
“…No significant effect was seen in 2 studies, including the Lathrop et al study [9,13]. MSC treatment led to a significant decrease in BAL IL-13 levels in 3 studies [9,15,17] (P < 0.001 to P < 0.05), including with treatment after allergen challenge [15], whereas BAL IL-13 levels were already low in controls in 1 study [25] and there was no significant change in 5 studies [12,13,20,23,24]. One short-term study that reported on IL-9 levels in BAL found a reduction with MSC treatment (P < 0.05) [26].…”
Section: Other Biochemical Outcomesmentioning
confidence: 91%
See 1 more Smart Citation